Development of 3ds MAX plugin tool for terrain generation - Song, Tao (2014)
3D terrain is of interest in various area of work (computer games and mixed reality), 3D terrain generation becomes a very interesting topic. Using a software tool to generate the 3D terrain model is a good way to solve the Terrain generation problem.